Empirical studies on the private value of Finnish patents - Charlotta Grönqvist (Bank of Finland, 2009)
Tiivistelmä 4 Acknowledgements 5 Introduction 9 Essay 1: The private value of patents by patent characteristics: evidence from Finland 43 Essay 2: Why does the private patent value differ by assignee? 61 Essay 3: Do the assignee's characteristics affect the private value of patents? 97 Essay 4: The optimal patent length is shorter than 18 years 131
URN:NBN:fi:bof-201408071686
Keywords: 330; Patent; Patentrecht; Kommerzialisierung; Wohlfahrtsanalyse; Innovationsdiffusion; Finnland